Determination of the iron-sulfur distances in rubredoxin by x-ray absorption spectroscopy. - Shulman, R G (1975)
The high intensity x-ray flux from the synchrotron radiation at the Stanford Synchroton Radiation Project has been used to study the extended x-ray absorption fine structure (EXAFS) of the iron-sulfur protein Peptococcus aerogenes rubredoxin. Absorption measurements were made from 7080 eV, which is below the K-edge of iron, to about 650 eV above the edge and structure was obtained over the entire region. By means of a model iron-sulfur compound for evaluating the phase shifts, the variation of the absorption above the edge of lyophilized, oxidized rubredoxin was converted to iron-sulfur distances. The data were fitted with a least squares program to a model in which three distances R3 were kept equal and the fourth R1 was allowed to differ. The mean square error was constant over a region of this parameter space, becoming twice as large at R3 = 2.217, R1 = 2.389 and R3 = 2.268, R1 = 2.108 A. These values, which are the extreme differences allowed by the present data, are definitely closer to being equal than those found by the determination of the x-ray diffraction crystal structure of the similar protein from Clostridium pasteurianum. However, the average distance from our experiment is in excellent agreement with the average distance from the crystal structure determination. Preliminary EXAFS measurements were also made on the oxidized rubredoxin in solution at pH 7.0. The spectra were unchanged, indicating that the average iron-sulfur distance change is less than 0.02 A. Upon reduction the average iron-sulfur bond length increased by about 0.05 A. Since the EXAFS measurements can give accurate determinations of distances in proteins both in crystals and solution, the technique should be widely applicable.